THE JUICES IN INFANT'S NUTRITION - T.N. Sorvacheva; E.A. Pyr'eva (Вопросы современной педиатрии, 2008)
The results of trials, investigating a tolerance to juices in children were summarized in this work. The correlation between criteria of tolerance and concentration of carbohydrates and osmolarity of juice was proved. Authors reviewed present guidelines on nutrition with juices in children of first year of life as a lure.Key words: juices, children's nutrition, lure.